2019
DOI: 10.1002/chem.201805677
|View full text |Cite
|
Sign up to set email alerts
|

(Li6Si5)2–5: The Smallest Cluster‐Assembled Materials Based on Aromatic Si56− Rings

Abstract: Extensive explorations of their potential energy surfaces, combined with high‐level quantum chemical computations, strikingly show that the lowest energy structures of the (Li6Si5)2–5 systems consist of 2–5 Si56− aromatic units, surrounded by Li+ counterions, respectively. These viable gas‐phase compounds are the pioneering reported cases of oligomers made by planar aromatic silicon rings. Based on the key evidence that these oligomers are energetically favored, and that their silicon rings aromaticity is thor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 46 publications
2
6
0
Order By: Relevance
“…For Li 8 Si 8 stoichiometry, both the global minimum and its three closest isomers (at 2.9, 4.5, and 5.9 kcal.mol −1 ) consist of two tetrahedral Si 4 moieties. The global minimum of Li 10 Si 9 and the second isomer (at 0.87 kcal.mol −1 ) consist of one pentagonal Si 5 and one tetrahedral Si 4 moieties, whereas Li 12 Si 12 global minimum consists of two Si 5 pentagonal rings, in agreement with previous reports from Yañez et al [31] . In all these assemblies, the lithium atoms lie between and around the silicon fragments (Figure 1 and Figures S3–S5 in the Supporting Information).…”
Section: Figuresupporting
confidence: 92%
See 1 more Smart Citation
“…For Li 8 Si 8 stoichiometry, both the global minimum and its three closest isomers (at 2.9, 4.5, and 5.9 kcal.mol −1 ) consist of two tetrahedral Si 4 moieties. The global minimum of Li 10 Si 9 and the second isomer (at 0.87 kcal.mol −1 ) consist of one pentagonal Si 5 and one tetrahedral Si 4 moieties, whereas Li 12 Si 12 global minimum consists of two Si 5 pentagonal rings, in agreement with previous reports from Yañez et al [31] . In all these assemblies, the lithium atoms lie between and around the silicon fragments (Figure 1 and Figures S3–S5 in the Supporting Information).…”
Section: Figuresupporting
confidence: 92%
“…The D 5h −Si 5 6− and T d ‐ Si 4 4− moieties are planar and spherical aromatic systems, [26] fulfilling the 4n+2 π‐electrons Hückel's and the 2(N+1) 2 Hirsh's electron‐counting rule, [27–30] respectively. Here, we report the theoretical prediction of the lowest energy structures of Li 8 Si 8 and Li 10 Si 9 for the first time, besides confirming the lowest energy structure of Li 12 Si 10 [31] . Remarkably, the first one consists of two T d −Si 4 4− units; the second of one Td −Si 4 4− and one D 5h −Si 5 6− units, and the third of two D 5h −Si 5 6− units, thus clearly showing a general growth pattern towards CAMs [1] .…”
Section: Figuresupporting
confidence: 77%
“…Two methods were used to explore the PES, the AUTOMATON program 61 and the KICK method. 62,63 In AUTOMATON, a probabilistic automata method built an initial population of 5 N individuals ( N is the number of atoms in the cluster of interest). Then this population evolved, through different generations, employing genetic operations.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Thus, for example, our group recently demonstrated that the global minima T d -Li 4 Si 4 and C 2v -Li 6 Si 5 consisting of Zintl Si 4 4− (tetrahedron) and Si 5 6− (pentagon) anions maintain their silicon motifs, almost unchanged, in the Li 8 Si 8 , Li 10 Si 9 , and Li 12 Si 10 combinations. 51,52 Furthermore, Li 6 Si 5 can be stacked to form a nanowire within a carbon nanotube. 53 These findings suggest that these small clusters could work as assembly blocks for CAMs, which is particularly interesting because these structural patterns have been identified in Li–Si materials.…”
Section: Introductionmentioning
confidence: 99%
“…[11b,15] D 5h Si 5 6À has been recognized as a suitable building block for larger clusters like (Li 6 Si 5 ) 2-5 systems. [16] Numerous strategies have been proposed to stabilize aromatic hydrocarbons with ten π-electrons. [17] These strategies often involve starting with six π-electrons rings, like benzene, and introducing four additional electrons through doping.…”
Section: Introductionmentioning
confidence: 99%